Formosan Subterranean Termite, Coptotermes formosanus Shiraki (Insecta: Isoptera: Rhinotermitidae) - Nan-Yao Su; Rudolph H. Scheffrahn (EDIS)
This document is EENY-121 one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: January 2000. Revised: May 2000.